Analysis of factors influence on the efficiency of design solutions - Chertkov, O. Yu.; Shumak, L.V.; Rasputnyi, D.S. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the analysis of factors that influence the effectiveness of design solutions in modern conditions of dynamic development, rapid digitalization and technological progress. The work identifies key factors that shape the success of project implementation, in particular external (economic, legislative, environmental, socio-political), internal (organizational, resource, personnel) and technical aspects. The emphasis is on the need to take into account such variables as the quality of planning, the innovativeness of the technologies used, the rational use of resources and the ability to adapt to unforeseen risks. Assessment of the effectiveness of design solutions in construction is a multifaceted process that includes economic, technological and organizational aspects. Literature analysis indicates the need to implement modern methods of cost estimation, innovative approaches to project management and ensuring high quality of design work to achieve optimal efficiency. The study reveals the importance of an integrated approach to project decision-making, which includes the analysis of economic efficiency, environmental sustainability and social impact. Particular attention is paid to the role of modern technologies, such as BIM systems and artificial intelligence tools, in increasing the accuracy of design, reducing implementation times and optimizing costs. It also considers practical aspects of risk management that arise due to the influence of external factors, such as legislative changes, market fluctuations or natural disasters. The article emphasizes the importance of joint management and responsibility in project decision-making, which contributes to the harmonization of relations between project participants, local communities and other stakeholders. It is found that the effectiveness of projects largely depends on compliance with the principles of sustainable development, which involves taking into account long-term economic, environmental and social consequences. The results of the study can be used to improve project management processes, increase their efficiency and ensure resilience in conditions of uncertainty. The proposed recommendations will be useful both for scientists studying project management issues and for practitioners involved in the development and implementation of projects in various areas of construction.